(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
In India Non-performing assets are one of the majorconcerns for banks.NPA is the best indicator for the health of the banking industry.In this paper we present about NPAs reflect the performances of banks. .NPAs isthe primary indicators of credit risk. NPAs are an inevitable burden on thebanking industry. Hence the success of a bank depends upon methods of managingNPAs. The Public Sector Banks have shown very good performance over the privatesector banks as far as the financial operations are concerned.